Desain Pembelajaran Kooperatif Tipe Card Sort pada Pelajaran Al-Qur'an Hadits Tingkat Madrasah Tsanawiyah (MTs) - Ida Tresnawati; Indi Milatul Maolah; Iis Khodijah (Indonesian Journal of Islamic Education Studies (INJURIES), 2023)
The card sort type cooperative learning model in the subject of Al-Qur'an Hadith MTs is in the form of learning by using pieces of paper formed like cards that contain information or subject matter then students group according to the index cards they have. After that students discuss and present the results of discussions about the material from the category of their group. Here the educator acts more as a facilitator and explains the material that needs to be discussed or material that the participants do not understand after the presentation is complete. Research with the title "Card Sort Cooperative Learning Design in Al-Qur'an Hadith MTs" is a type of qualitative research, with a library research or literature research approach. The results of the study reported that when the teacher used the card sort type learning model, students were more active in following the Al-Qur'an Hadith subject. In addition to increasing student activeness, the card sort type cooperative learning model is felt to be a differentiating thing. The atmosphere seemed fun, training students in expressing the answers asked by the teacher. Students also absorb the material presented in the Al-Qur'an Hadith subject better. Keywords: Learning Design; Co-Operative Card Sort; Al-Qur'an Hadith Lesson.